Determinan Kejadian Malaria di Wilayah Endemis - Hasyim, Hamzah; Camelia, Anita; Fajar, Nur Alam (UI Scholars Hub, 2014)
Kabupaten Lahat adalah salah satu wilayah endemis malaria di Sumatera Selatan dengan prevalensi 16,4% dan Annual Malaria Incidence 22,08. Tujuan penelitian ini untuk mengetahui faktor risiko lingkungan dengan kejadian malaria. Faktor risiko lingkungan genangan air (breeding place) berhubungan dengan kejadian malaria dengan nilai p= 0,000. Analisis multivariat menemukan determinan utama kejadian malaria adalah breeding place di sekitar rumah responden dengan odds ratio (OR) = 5,034 dan 95% CI = 2,65 _ 9,56. Responden yang tinggal di sekitar breeding place berisiko 5,03 kali lebih besar untuk menderita malaria dibandingkan dengan responden yang di sekitar rumah tidak terdapat breeding place setelah dikontrol variabel jarak rumah ke breeding place, ventilasi rumah, penggunaan kelambu, penggunaan obat anti nyamuk, dan kebiasaan keluar rumah pada malam hari. Lahat district is one of the malaria endemic area in South Sumatra Province with a prevalence of 16.4% and Annual Malaria Incidence of 22.08. The case control reports were carried out of 240 respondents. This study aimed to understand the relationship among of environmental risk factors with the incidence of malaria. After primary data collection followed by processing and data analysis in a multimedia laboratory. There was association between breeding place and malaria cases (p value= 0.000). The results of multivariate analysis of variables revealed the determinant risk was breeding place, with OR = 5.034 and CI 95%= 2.65 _ 9.56. Respondents who live around the breeding place has 5.034 times chance of affected malaria compared with respondents around the house there are no breeding place after the controlled distance to the breeding place house, use of mosquito nets, use of anti-mosquito, and habits out of the house at night variables.